DISIPLIN KERJA DAN LINGKUNGAN KERJA DALAM MEMPENGARUHI KINERJA KARYAWAN PADA PT. BUMI SUBUR 5 KECAMATAN MLANDINGAN DENGAN MEDIASI VARIABEL KEPUASAN KERJA - Masruroh, Rosa Dwi Nafiola; Arief, Mohammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The purpose of this study was to analyze the influence of work discipline and work environment variables in influencing employee performance at PT BumiSubur 5 at MlandinganSubdistrict with job satisfaction as a mediating variable by using the Partial Least Square (PLS) Structural equation model. The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that work discipline has a significant effect on job satisfaction (H1 accepted), work environment has a significant effect on job satisfaction (H2 accepted), work discipline has a significant effect on employee performance (H3 accepted), work environment has a significant effect on employee performance (H4 rejected), job satisfaction has a significant effect on employee performance (H5 accepted), work discipline has a significant effect on employee performance through job satisfaction (H6 rejected), and work environment has a significant effect on employee performance through job satisfaction (H7 accepted).